The Graymail Problem Anew in a World Going Dark: Balancing the Interests of the Government and Defendants in Prosecutions Using Network Investigative Techniques (NITs) - Chen, Christine W. (Science and Technology Law Review, 2018)
As technology moves toward encryption, law enforcement has turned to creative methods to apprehend criminals attempting to hide or obscure their digital wrongdoings. One such method is the network investigative technique (NIT), which essentially operates by sending a tracking program to users’ computer systems to uncover their real IP addresses. Judges can authorize the deployment of NITs through warrants. With the jurisdictional hurdle limiting the reach of such warrants removed by the recent change in Rule 41 of the Federal Rules of Criminal Procedure, the usage of NITs is certain to become more commonplace. However, courts are uncertain about how to treat evidence obtained through NITs, especially with respect to whether defendants are entitled to the full NIT code used against them in the course of discovery. If defendants can access the full code, they could threaten to divulge it to the general public unless prosecutors drop the criminal charges. But if prevented from accessing the code under any circumstances, defendants may be locked into an unfair trial. This Note suggests that courts will need to reformulate the test traditionally used to balance the government’s interests and defendants’ due process rights with regard to sensitive or confidential information to create a general presumption against releasing the full NIT code.